THE ROLE OF CLIMATE CHANGE IN THE DECLINE OF NARRAGANSETT BAY WINTER FLOUNDER - Langan, Joseph A. (DigitalCommons@URI, 2021)
Winter flounder (Pseudopleuronectes americanus) has historically supported productive commercial and recreational fisheries throughout its range in the northwest Atlantic. As a small flatfish that inhabits estuaries, bays, and the coastal zone, this species is vulnerable to shifting environmental conditions in many of the habitats critical to its life cycle. At the southern edge of the species range, the Southern New England/Mid-Atlantic Bight winter flounder stock entered a steep decline during the 1980s following a period of overfishing. Despite repeated reductions in harvest during the proceeding decades, the population has yet to recover. A decreasing trend in recruitment has led to speculation that increased mortality during the early life cycle is preventing this stock from rebuilding. While it is well known that environmental stressors, predation, competition, and anthropogenic disturbances all can impact the survival of juvenile flounder, it remains unclear which of these factors are most important in regulating population productivity. To answer this question for the Narragansett Bay, Rhode Island winter flounder subpopulation, part of the Southern New England/Mid-Atlantic Bight stock, this dissertation aims to model the winter flounder life cycle and its patterns of habitat use to better understand the population dynamics and future recovery potential of this climate-challenged species. The first chapter aimed to model the winter flounder early life cycle to uncover patterns of population regulation and identify trends in juvenile mortality. Using a structural equation model fit to abundance indices of 29 year classes progressing through seven life stages gathered from multiple scientific surveys in Rhode Island waters, it was determined that winter flounder year class strength does not appear to be fully determined until cohorts join the spawning population. However, an increasing trend in mortality was identified during the first summer of life that was linked to rising summer temperatures, hypoxia, ...